SOCIAL SUPPORT FROM FAMILY AND FRIENDS: DISCOURSE OF PEOPLE WITH SUICIDAL BEHAVIOR - Isabela Carolyne Sena de Andrade; Nadirlene Pereira Gomes; Cíntia Mesquita Correia; Josinete Gonçalves Lírio; Ionara Rocha das Virgens; Nildete Pereira Gomes; Deise da Silva Monteiro (Universidade Federal do Paraná, 2019)
Objective: To identify the elements that favor the social support from family and friends to people with suicidal behavior. Method: Qualitative study with 18 individuals undergoing therapeutic follow-up in the Center for Suicide Research and Prevention (NEPS) of Salvador, Bahia, Brazil. Data was collected from March to August 2018 and organized based on the Collective Subject Discourse methodology. Results: The study showed that affectional bonds, previous experiences of mental suffering, empathy and understanding of suicidal behavior are elements that reflect significant social support from family and friends. Final Considerations: Knowledge and use of these elements may support actions for the prevention of suicide, since health professionals responsible for care to people with suicidal behavior may develop strategies aimed at strengthening social support.